Advances in Clinical Sample Preparation for Identification and Characterization of Bacterial Pathogens Using Metagenomics - Bachmann, Nathan L.; Rockett, Rebecca J.; Timms, Verlaine Joy; Sintchenko, Vitali (Frontiers in Public Health, 2018)
Whole genome sequencing (WGS) is beginning to play a major role in communicable disease control through outbreak tracing, laboratory surveillance and diagnostics. However, WGS has traditionally relied on microbial culture in order to isolate pathogen specific DNA for sequencing. This has severely limited the application of whole genome sequencing on pathogens that have fastidious culturing requirements. In addition, with the advancement of new technologies including GeneXpert, public health laboratories are increasingly relying on non-culture based techniques and testing for pathogens is done directly from clinical samples for an increasing number of diagnostic tests. Public health laboratories are transitioning away from culturing to improve turnaround time for diagnostics and reduce costs by minimizing culturing facilities. To stay relevant, public health laboratories need ongoing research to develop culture-independent whole genome sequencing (CI-WGS) that aim to provide a microbial genome without having to culture an isolate. However, there are challenges when attempting to sequence a specific organism from clinical samples including high levels of contaminating DNA from the host and/or other microorganisms. Several methods have been developed to selective lysis host cells and/or separate specific organisms from a clinical sample. These methods are further combined with enrichment techniques to increase the concentration of DNA. This review summarizes the different approaches of CI-WGS that have been used in clinical laboratories and the application of CI-WGS to specific infections.